# 4x+4=9x-36

## Simple and best practice solution for 4x+4=9x-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 4x+4=9x-36 equation:

Simplifying 4x + 4 = 9x + -36 Reorder the terms: 4 + 4x = 9x + -36 Reorder the terms: 4 + 4x = -36 + 9x Solving 4 + 4x = -36 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 4 + 4x + -9x = -36 + 9x + -9x Combine like terms: 4x + -9x = -5x 4 + -5x = -36 + 9x + -9x Combine like terms: 9x + -9x = 0 4 + -5x = -36 + 0 4 + -5x = -36 Add '-4' to each side of the equation. 4 + -4 + -5x = -36 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = -36 + -4 -5x = -36 + -4 Combine like terms: -36 + -4 = -40 -5x = -40 Divide each side by '-5'. x = 8 Simplifying x = 8

### See similar equations:

| 9-(12-8x)=4x-(51+8x) | | 2x^4+3x^3+3x-2=0 | | (7x-2)(7x+2)-(5y-2)(5y+2)=0 | | 2x(x+8)=-30 | | x^2+36=12x | | -2x^2+x=0 | | 9x^2-6x-4=-5 | | 2x^2+3x-9=0 | | y=5x^2-11 | | 3x^2+x-4=0 | | 2x-4=4(x-5) | | 2p^2-3p-2=0 | | x^2-2x+1=18 | | 2(x+1)=6x-46 | | 28+2x=5x+7 | | 6+3x=5x | | -7-1x=8 | | X-12=3x+4 | | 0.5x-8=14+0.5x | | -2=-4x+24 | | -2(8z+2)=-7z+7 | | -3-(-4x)=-4x-5 | | x=35-4x | | 2(2x-6)=8x | | 12x-18=10x+4 | | 2(6x-9)=12x-18 | | x+48=-x | | -(10-x)=3x+12 | | 2x^3-6x^2-6x-18=0 | | 5x+7y=63 | | 4x-60=2x+30 | | 3a-5b=0 | | 6p-q=40 | | 8y=24+2y | | 5h-9=16+6h | | 3x-3=-4x | | 6(x+10)=-12 | | 2y+4-y=16 | | 7x+5=4x+5+3x | | x^5+x^3-6x=0 | | y=63x^6-21x^8 | | 4(-2x+3)=100 | | 3y-2(17)=8 | | .5x=10 | | 16.35-(-20.95)= | | 16=-6-2x+31-3x | | 5x+3x^2=12 | | 7x+1=29 | | 5x-12=8-5x | | -2-7x=-72 | | (2y-7)+(3x+4)i=1+i | | 5+4=19 | | -17W+40=8W^2+5w | | (3x-4)(x-6)=17 | | 3x-4=6x-19 | | 8x^2-14x+6=0 | | y^2-25y=0 | | 3x+6=0 | | -2+-7x=-72 | | 6x+7=49 | | 4x+5=23 | | 4x+2=x-7 | | x-(-4)=9 | | x-(-2)=-15 | | 5x-7=2x-1 |